Sistem Kendali Jarak Tempuh Quadcopter Menggunakan Metode Proportional Integral Derivative - Enno Roscitra Oktaria; Gembong Edhi Setyawan; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Quadcopter is one of Unmanned Aerial Vehicle (UAV) robots that has the ability to maneuver in various directions and flexible to explore a narrow area. These capabilities can be optimized for the benefits by building automated navigation systems on the quadcopter. One of them is designing a precision control system of quadcopter position movement using a PID (Proportional Integral Derivative) method. Tuning of PID parameters using the Ziegler Nichols oscillation method. From the test result of PID parameter tuning, the system response oscillates stably when the value of Ku = 0,07 and Pu = 0,092, so that the movement control in the pitch and roll angle obtained Kp = 0,042; Ki = 0,046; and Kd = 0,0115. From the observation of position accuracy testing, it shows that the control system using PID yields an error rate of 4,99% and the time required for the system to enter Â± 2% of the steady state or settling time of 0,4145 s. The error rate and settling time are obtained based on the average results of each test that has been done.